2004
DOI: 10.1002/jbm.a.30224
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol‐derivatized polyurethane: Characterization and endothelial cell adhesion

Abstract: Endothelialization of synthetic surfaces has been challenging with limited success thus far. We investigated the hypothesis that covalent attachment of cholesterol to polyurethane via the urethane nitrogen groups would create a high-affinity surface for attachment and adhesion of endothelial cells. Cholesterol was covalently bound to the polyether polyurethane, Tecothane, by first derivatizing the polyurethane nitrogen groups with bromoalkyl side chains, followed by reacting mercapto-cholesterol to the bromoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
(80 reference statements)
4
33
0
Order By: Relevance
“…Thus, numerous studies have addressed this deficiency via several types of PU surface modification. [40][41][42][43][44][45][46]. PU has been treated with gas plasma to improve EC adhesion and growth [42], although such a treatment also risks increasing the non-specific attachment of undesirable proteins and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, numerous studies have addressed this deficiency via several types of PU surface modification. [40][41][42][43][44][45][46]. PU has been treated with gas plasma to improve EC adhesion and growth [42], although such a treatment also risks increasing the non-specific attachment of undesirable proteins and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine aortic endothelial cells (BAEC) were obtained as previously described [20] and cultured in DMEM (Mediatech, Inc., Herndon, VA, USA) supplemented with 10% fetal calf serum. Primary human umbilical vein endothelial cells (HUVEC, Clonectics, San Diego, CA), 4th passage, grown to near confluence were cultured on 1% gelatin-coated 24 well plates.…”
Section: Methodsmentioning
confidence: 99%
“…A number of novel alterations to PU has been attempted to alleviate these problems. Our group synthesized and characterized a bulk-modified PU configured with mercapto-cholesterol (PU-Chol) via bromoalkylation of hard segment urethane nitrogen [4, 13]. Analysis of the physical properties of PU-Chol films revealed that the addition of cholesterol moieties to PU increased the surface hydrophobicity and decreased the surface roughness [4].…”
Section: Introductionmentioning
confidence: 99%